Impacts of freight logistic hub in a densely populated city: A study on Tejgaon Truck Stand of Dhaka (Journal of Bangladesh Institute of Planners, 2025)
Tejgaon truck stand was an important logistic hub for Dhaka city for about a century. Initially it was on the outskirt of the city, as the city was much smaller spreading up to Tejgaon area on the northern periphery. However, with the growth of Dhaka city, it became surrounded by commercial and mixed land uses, and Tejgaon area became one of the central places of the city. Though the government started to control truck movement in the city during the daytime, the location of such a logistic hub in a central city area created several problems. This study looked into the environmental and traffic impacts of the logistic hub using primary data and secondary sources. The study identified noise pollution, traffic congestion, traffic speed, variability in traffic flow and road space scenarios with and without trucks. Existing policies and stakeholders’ views were also analysed through thematic analysis. The results unveiled the negative impacts of the logistic hub through noise pollution at night time and increased congestion on the access road and arterial road till midnight. Traffic speed and flow were highly affected due to illegally parked trucks on the adjacent roads caused by shortage of space within the truck stand. The analysis and discussion showed that relocation of this logistic hub could improve the traffic flow and reliability of the road traffic in the area. However, the stakeholder groups had conflicting opinions on relocation and in-situ improvements for this hub, which requires further investigation for a fruitful solution.JBIP, Vol. 17, 2024, pp. 75-100